Use of Prototyping Technology as an Aid for Oral Rehabilitation - Luiz C. Cardoso; Cecília A. C. Zavaglia; Guinea B. C. Cardoso (Archives of Current Research International, 2017)
The purpose of this manuscript is report the novel prototyping device for intra-oral rehabilitation in patients with atrophic and extended areas of bone loss. Virtual maxilla models were produced using 3D reconstruction of CT scan, using InVersalius Software. On virtual models was designed the customized device, with determinate characteristics such as porosity, pore range, wall thickness and extension and also number and position of hexagonal attachment. Maxilla models and customized devices were printed using additive manufacturing technology to analyze the compatibility of virtual characteristics. Mechanical flexural test and cytotoxicity tests were produced to valid the chosen material alloy. The results demonstrate viability of the novel device. Ti-6Al-4V alloy presents compatible flexural strength with the maxilla bone, and do not show any characteristic of cytotoxicity. The proposed design shows a saddle juxtaposed on the mandibular crest, allowing a homogenous tension distribution; a variable numbers and positions of screws with hexagonal attachment. Due the flexible screw design it brings an improvement to an easy prosthesis fixation, and since the hexagonal attachment is compatible with commercial parts it enables a cost reduction and increase the viability. The novel device has suitable characteristics to become a feasible option for patients with atrophic oral regions.